Exploring the perceived level of satisfaction with the quality of library services in university libraries in Tanzania - Kaishe-Mulungu, Kaishe-Mulungu Dativa; Angelo, Consolata; Lwehabura, Mugyabuso J.F. (Access: An International Journal of Nepal Library Association, 2025)
This study aimed at exploring the perceived level of satisfaction with the quality of library services (QLS) on university libraries in Tanzania. Specifically, the study analysed the extent to which the library services influences library users’ level of satisfaction and assess how library users perceive their satisfaction with the quality of library services. The study used a cross-sectional research design. Simple random sampling and purposive sampling procedures were used to select 397 respondents and 68 key informants respectively. Questionnaires and interviews were used to collect data. The data were analysed using SPSS tool version 20th and content analysis. The key findings revealed that 75% of library staff were approachable, polite, friendly, empathetic, available to respond timely to users needs. Moreover, 61.2% indicated that time provided for using the library was adequate for users and results from binary logistic regression shows that noise, poor photocopy services, lack of air condition, lack of weekend services and early closing time had statistically significance influence on users satisfaction with library services. Moreover, the study found that 38% opined that a good library provides users with advisory services; Sufficient collection was mentioned by 33.8%. Seating arrangements and attractive environment to learn was rated at 47.9%. However, 13% disagreed that a good library provides reservation/booking services. The study therefore concluded that library users were satisfied by the university libraries services in terms of library collection, library environment, staff, facilities and services provided. The study recommended that library management should strive to have a number of services some of which include current collection/facilities, conducive environment, trained staff, adequate furniture and so on.